KRISIS KEWANGAN GLOBAL: KESTABILAN DAN KARAKTERISTIK UNIK PERBANKAN ISLAM: Global Financial Crisis: Stability and Unique Characteristics of Islamic Banking - Mohamad, Mohammad Taqiuddin; Borhan, Joni Tamkin; Sulaiman@Mohamad, Ahmad Azam (Jurnal Syariah, 2014)
The global financial crisis is a blessing to the Islamic banking industry. Crisis that erupted not only be able to put this industry as the focus, but make it a vital alternative to the global financial system. Unique characteristics and resilience of belonging has prompted global financial bodies like the World Bank and the International Monetary Fund (IMF) to set up a special committee to study the strength and uniqueness infrastructure owned by Islamic banking. Based on the above issues and problems, this study will use three main method of analysis such as descriptive, analytical and comparison to analyze the distinguishing characteristics of Islamic banking compare with conventional banking. Further, this characteristics will be linked with the contribution of Islamic banking to the overall financial stability functions. The study found that the stability and soundness of Islamic banking in the face of the global financial crisis due to the principle of prohibiting riba, implementing profit and loss sharing (PLS) and the concept of mark-up price. However the main obstacles exist that make Islamic banking is not completely stable and robust due to the industry still operates within the conventional framework. This barrier becomes a major constraint to Islamic banking to entirely implement the unique features of Islamic banking as suggested by Islamic scholars based on the Syariah principles.